Anesthesia - Antunes, Luis (Henry Stewart Talks, 2016)
Anesthesia in lab animals sciences: reasons and concerns, Different stages and components of general anesthesia, Groups of drugs and side effects, Injectable vs. inhalational agents, Equipment, Choosing the best practice